Does the Dream of Home Ownership Rest upon Biased Beliefs? A Test Based on Predicted and Realized Life Satisfaction - Reto Odermatt; Alois Stutzer (Institute of Labor Economics (IZA), 2020)
The belief that home ownership makes people happy is probably one of the most widespread intuitive theories of happiness. However, whether it is accurate is an open question. Based on individual panel data, we explore whether home buyers systematically overestimate the life satisfaction associated with living in their privately owned property. To identify potential prediction errors, we compare people's forecasts of their life satisfaction in five years' time with their current realizations. We find that, while moving into a purchased dwelling is associated with higher life satisfaction, people systematically overestimate the long-term satisfaction gain. The misprediction therein is driven by people who follow extrinsically-oriented life goals, highlighting biased beliefs regarding own preferences as a relevant mechanism in the prediction errors.
Keywords: D12; D83; D90; I31; R20; 330; beliefs; home ownership; housing tenure; life goals; life satisfaction; projection bias; subjective well-being; intuitive theories of happiness; utility prediction